Walls, borders, boundaries : spatial and cultural practices in Europe - Ward, Janet, 1963- (Spektrum (New York, N.Y.), 2012)
How is it that walls, borders, boundaries-and their material and symbolic architectures of division and exclusion-engender their very opposite? This edited volume explores the crossings, permeations, and constructions of cultural and political borders between peoples and territories, examining how walls, borders, and boundaries signify both interdependence and contact within sites of conflict and separation. Topics addressed range from the geopolitics of Europe's historical and contemporary city walls to conceptual reflections on the intersection of human rights and separating walls, the memor.